Therapeutic Management of a Substantial Pelvic Aneurysmatic Bone Cyst Including the Off-Label Use of Denosumab in a 35-Year-Old Female Patient - D. Ntalos; M. Priemel; C. Schlickewei; D. M. Thiesen; J. M. Rueger; A. S. Spiro (Case Reports in Orthopedics)
Aneurysmal bone cysts (ABC) are benign bone tumors, which are highly vascularized. The main course of treatment is curettage followed by bone grafting or cement insertion. Still recurrence remains a main problem for patients. Denosumab is a monoclonal antibody, which acts as an inhibitor of the RANK/RANKL pathway, diminishing bone turnover. Recent case reports have shown that Denosumab can be a promising therapeutic agent for people suffering from therapy-resistant ABC. We report the case of a 35-year-old female patient presenting with a pronounced ABC of the pelvis. Since the tumor was inoperable, Denosumab was administered, leading to a significant shrinkage of the lesion, which allowed surgical intervention. Upon recurrence, Denosumab was restarted putting the patient once more into remission. Follow-up was four years overall with a clinical and radiological stable disease for fifteen months after final discontinuation of the monoclonal antibody. Therefore, our case further underlines the potential of Denosumab in the treatment of ABC.